Compiling for massively parallel architectures: a perspective - Feautrier, Paul (Microprocessing and microprogramming, 1995)
The problem of automatically generating programs for massively parallel computers is a very complicated one, mainly because there are many architectures, each of them seeming to pose its own particular compilation problem. The purpose of this paper is to propose a framework in which to discuss the compilation process, and to show that the features which affect it are few and generate a small number of combinations. The paper is oriented toward fine-grained parallelization of static control programs, with emphasis on dataflow analysis, scheduling and placement. When going from there to more general programs and to coarser parallelism, one encounters new problems, some of which are discussed in the conclusion.